Identifikasi Pemberdayaan dan Sertifikasi Halal Pada UMKM oleh Lembaga Zakat di Bangkalan Madura - Choiri, Muttaqin; Ma'adi, Alan Su'ud (Fakultas Syariah INSURI Ponorogo, 2023)
Indonesia Law Number 33 of 2014 concerning Halal Product Guarantee emphasizes that food, medicine, cosmetics and other products must be halal certified, which not only applies to products of large companies, but also targets MSME. Apart from going through a special self-declaration route for simple products for free, most MSMEs such as processed products from slaughter, pentol sellers, meatballs need to get service facilitation, which can be taken from social institution posts, such as zakat, infaq and shodaqaoh. Zakat management institutions are one of the institutions that collect, manage and distribute social religious funds, which are intended to improve economic levels, either consumptively or productively. With approximately 166,000 MSMEs in Bangkalan Regency, the participation of social religious institutions is needed to support the halal certification policy. This research used qualitative method, descriptive analytical with empirical approach. Data collection through interviews, observations and documentation studies at zakat management institutions in Bangkalan. The results showed that zakat management institutions in Bangkalan have not facilitated the halal certification process for MSME, apart from the fact that there has been no socialization from zakat institutions at the central level to play an active role in the program, also concerns about the hadd al-kifayah standard for mustahiq need to be emphasized so that the limits of zakat distribution for empowerment and acceleration of halal certification programs are right on target and right based on sharia provisions, it is necessary to identify the income of MSMEs so that the mustahiq category can still be accommodated.